Low-Temperature Specific Heats of the beta and zeta Phases in Equiatomic AgZn - Abriata, J. P.; Bressan, O. J.; Luengo, C. A.; Thoulouze, D. (American Physical Society, 1970)
Fil: Abriata, J. P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina